Implementation of the Dengue Fever Surveillance System at the Klungkung District Health Office - Sukmawathi, Ni Luh Ayu; Sawitri, Anak Agung Sagung; Megawati, Ida Ayu (Newinera Publisher, 2024)
This evaluation aims to find out how to implement and analyze problems in the dengue surveillance system. The evaluation was carried out in March-June 2023 using the concepts of input, process, output and surveillance attributes. Data collection was carried out on 1 health service officer, 4 community health center officers by interviewing and observing using a questionnaire. The health centers were selected based on the criteria for accuracy in collecting reports. Data is presented in the form of graphs, tables and narratives. According to interviews and observations, the findings relate to input, process, output and surveillance attributes. All health center and health service officers (100%) have never received training/orientation. There are (25%) community health center officers who are late in collecting reports, this is an obstacle to data collection by the Health Service. Health Service officers rarely carry out monitoring related to the collection of reports by the Puskesmas, but the reasons for delays are still communicated. 100% of community health centers have investigated risk factors, but the community health center network does not report suspect cases. As many as (100%) officers do not know how to analyze data based on person, place and time and all officers (100%) have not presented the results of data analysis as a form of information about dengue fever. This causes the type, components and attributes of surveillance, namely representative implementation, to not be optimal. The implementation of the surveillance system is not in accordance with the types, components and attributes of surveillance.